The frequency of pulmonary hypertension in patients with juvenile scleroderma - Amra Adrovic; Funda Oztunc; Kenan Barut; Aida Koka; Refet Gojak; Sezgin Sahin; Tuncalp Demir; Ozgur Kasapcopur (Biomolecules & Biomedicine, 2015)
Juvenile scleroderma (JS) represents a rarely seen group of connective tissue diseases with multiple organ involvement. Cardiac involvement in JSS is well known and, although rare in children, it may be an important cause of mortality and morbidity. Therefore, an early determination of cardio-vascular and pulmonary involvement is of the most relevance to reduce the mortality in patients with juvenile scleroderma. The aim of the study was to explore the non-invasive methods (Doppler echocardiography, pulmonary function tests), Forced vital capacity (FVC) and Carbon monoxide diffusion capacity (DLCO) in the assessment of the cardiopulmonary involvement in patients with JS. The assessment of pulmonary arterial pressure (PAP) and risk factors for pulmonary arterial hypertension (PAH) were made by the measurement of maximum tricuspid insufficiency (TI), end-diastolic pulmonary insufficiency (PI), ratio of acceleration time (AT) to ejection time (ET) (AT/ET), right atrial pressure (RAP) and contraction of vena cava inferior during inspiration. Thirty-five patients with confirmed JS were included in the study. The mean age of onset of the disease was 9.57 years (median 10 years, range 2-18 years). The mean disease duration and follow-up time was 2 years (median 1 year, range 0.5-8 years) and 3.57 years (median 2 years, range 0.5-14.5 years), respectively.The values of all the analyzed parameters including TI, PI, AT/ET, PAP, FVC and DLCO were found to be within normal ranges in all the patients tested, confirming an uncommonness of cardiopulmonary involvement in patients with juvenile scleroderma.